2004
DOI: 10.1097/00004770-200403000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultrasound, With and Without Water Spray Cooling, on Removal of Posts Cemented With Resin or Zinc Phosphate Cements

Abstract: The efficacy of ultrasound, with and without water spray, was evaluated in vitro on the amount of force necessary to dislodge posts cemented with resin or zinc phosphate. Forty-two samples were divided into six groups: groups 1, 2, and 3, posts cemented with zinc phosphate; groups 4, 5, and 6, posts cemented with resin (Panavia F); groups 1 and 4 (controls), no ultrasound; groups 2 and 5, ultrasound without water spray; and groups 3 and 6, ultrasound with water spray. The Instron testing machine was used. Ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
7

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 12 publications
1
39
0
7
Order By: Relevance
“…According to Berbert et al (13), the use of ultrasound for 2 and 5 min reduces the force necessary to remove cast metal posts cemented with zinc phosphate by 30-35% when compared to removal of the same type of intraradicular posts without ultrasound. Garrido et al (14), however, used resin cement in a similar trial and did not find any statistically significant difference between the group for which ultrasound and irrigation were used and the group for which ultrasound was not used.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Berbert et al (13), the use of ultrasound for 2 and 5 min reduces the force necessary to remove cast metal posts cemented with zinc phosphate by 30-35% when compared to removal of the same type of intraradicular posts without ultrasound. Garrido et al (14), however, used resin cement in a similar trial and did not find any statistically significant difference between the group for which ultrasound and irrigation were used and the group for which ultrasound was not used.…”
Section: Discussionmentioning
confidence: 95%
“…Tukey critical value = 0.73135. alternative technique for removal, either alone or in combination with other techniques (9)(10)(11)(12)14). The development of improved procedures for currently used techniques is as important as the development of new techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Resin cements are not friable and do not tend to produce microfractures due to ultrasonic vibration (106). It was suggested that the absence of a water spray seems to increase the action of US when applied to posts cemented with resin cements, possibly because of the increase in heat (107). This is helpful information, as it has been observed that the capacity of adhesion of a resin cement, and consequently mechanical retention, gradually reduces with the number of thermal cycles (108).…”
Section: Root Canal Postsmentioning
confidence: 99%
“…Serious bone damage was shown at higher temperatures or for longer application times. Many in vitro studies have measured the TR on the external root surface during the removal of intracanal posts using ultrasonic devices (22)(23)(24)(25). Three cases of severe burn injuries after ultrasonic removal of posts were reported (26).…”
mentioning
confidence: 99%